2017
DOI: 10.17576/jsm-2017-4608-06
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Kualiti Air daripada Sistem Penuaian Air Hujan di Kolej Ungku Omar, UKM Bangi

Abstract: ABSTRAK Kajian ini bertujuan untuk menentukan tahap kualiti air hujan di dalam Sistem Penuaian Air Hujan iaitu MyRAWAS yang dibina di 2°C-28.6°C, 6.18-6.36, 0.93-3.06 ntu, 1.0-4.6 mg/L, 6.21-8.29 mg/L, 0.21-0.43 temperature, pH, turbidity, TSS, DO, BOD,[3][4][5][6][7] respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…According to Hashim et al [38], the rainwater quality in Malaysia satisfies the drinking water standard. The finding is supported by Asman et al [39]. Based on their study in Bangi; rainwater harvesting can be supplied for domestic purposes and as well as drinking water, but with additional treatment.…”
Section: East Malaysia Climate and Rainwater Blessingmentioning
confidence: 58%
“…According to Hashim et al [38], the rainwater quality in Malaysia satisfies the drinking water standard. The finding is supported by Asman et al [39]. Based on their study in Bangi; rainwater harvesting can be supplied for domestic purposes and as well as drinking water, but with additional treatment.…”
Section: East Malaysia Climate and Rainwater Blessingmentioning
confidence: 58%
“…The removal of heavy metals is attributed to the high level of suspended solids and metal complexes in POME which may act as a natural coagulant. The suspended solids and metal complexes improve the charged exchange and accelerated the adsorption and deposition of dissolved heavy metals in wastewater [36][37][38][39][40]. This study showed more efficient removal than Banch et al [8] for Fe 2+ , As 3+ , Zn 2+ , Cr 2+ , Cu 2+ , Co 2+ , and Cd 2+ .…”
Section: Heavy Metal Analysismentioning
confidence: 59%
“…October 2016 November 2016 Quality of rainwater is influenced by several factors such as the locality and neighbour ing activities, collection system and storage material, rainfall time span, and interval of wet and dry climate (Che- Ani, Shaari, et al, 2009;Kasmin, Bakar, et al, 2016;Yaziz, Gunting, et al, 1989;Despins, Farahbakhsh, et al, 2009;Shaheed, Wan Mohtar, et al, 2017). In general, urban areas with more industrial activities will have more suspended debris in the atmosphere which will be carried during rainfall (Man, 2015). Material for storing containers for harvested rainwater, such as plastic cisterns is more acidic as compared to a concrete storage (Despins, Farahbakhsh, et al, 2009).…”
Section: September 2016mentioning
confidence: 99%